Participation and provision in arts & culture – bridging the divide. Issue 1 (2nd January 2016) - Evans, Graeme
ABSTRACT: Successive policies and efforts to increase participation in a range of arts and cultural activities have tended to focus on the profile and attitude of individuals and target groups in order justify public – and therefore achieve more equitable – funding. Rationales for such intervention generally reflect the policy and political regime operating in different eras, but widening participation, increasing access and making the subsidised arts more inclusive have been perennial concerns. On the other hand, culture has also been the subject of a supply-led approach to facility provision, whether local amenity-based ("Every Town Should Have One" – Lane, 1979. Arts centres – every town should have one. London: Paul Elek), civic centre or flagship, and this has also mirrored periodic growth in investment through various capital for the arts, municipal expansion, urban regeneration, European regional development and lottery programmes. Research into participation has consequently taken a macro, sociological, "class distinction" approach, including longitudinal national surveys such as Taking Part, Target Group Index, Active People and Time Use Surveys, whilst actual provision is dealt with at the micro, amenity level in terms of its impact and catchment. This article therefore considers how this situation has evolved and the implications for cultural policy, planning and research by critiquing successive surveys of arts attendance and participation and associated arts policy initiatives, including the importance of local facilities such as arts centres, cinemas and libraries. A focus on cultural mapping approaches to accessible cultural amenities reveals important evidence for bridging the divide between cultural participation and provision.